PENAMBAHAN AIR PERASAN JERUK NIPIS (Citrus aurantiifolia) SEBAGAI ACIDIFIER TERHADAP BOBOT RELATIF, PANJANG RELATIF USUS HALUS DAN KONSUMSI PAKAN AYAM BROILER - Aditya Surya Pratama; Turrini Yudiarti; Isroli Isroli (Universitas Wahid Hasyim, 2019)
The aim of the research was to improve the relative weight, relative length and dietary of the broilers’ small intestine (duodenum, jejunum, ileum) with the slight squeeze of the lime as acidifier. The research was conducted according to completely randomized design with 3 treatments and 6 replications (each experimental unit consisted of 5-6 broilers). Treatments were T0 (normal), T1 (5mL lime + 1000mL water), and T2 (10mL + 1000 mL water). Relative weight and relative length of the small intestine were not affected by the addiction of the lime, either dietary was not significantly affected by the addiction of the lime on the water as acidifier. The lime could not improve the dietary of the broiler. Keywords: Broiler, Lime, Acidifier, Small Intestine, Dietary.